MORPHOLOGICAL TENSE AS THE FORM OF HUMAN'S INTERPRETATION OF ONTOLOGICAL TIME - Nakonechna, L. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The main subject of the article is the morphological tense as the form of human's interpretation of time, which is one of ontologica lcategories. Semantic and functional characteristics of grammatical category of time, as well as lingual and syntactic time are analysed by the author.The nature of absolute, relative and transposed use of verb's tense forms has been described at thework.